2019
DOI: 10.3390/cancers12010023
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Is Superior to Direct Acting Antiviral Therapy in Tertiary Prevention of Early Recurrence of Hepatocellular Carcinoma

Abstract: The elimination of chronic hepatitis C infection (CHC) by pegylated interferon plus ribavirin (Peg-IFN/RBV) decreases hepatocellular carcinoma (HCC) recurrence rate. However, the tertiary prevention of HCC recurrence by direct acting antiviral agents (DAA) remains controversial. This study aims to compare the tertiary prevention effect between DAA and Peg-IFN/RBV in CHC-HCC patients. Three hundred and one patients who received curative HCC treatment were retrospectively recruited. The recurrence incidence rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…Of the 49 articles that we included, 39 reported adjusted HRs or IRRs for the outcomes of interest and were included in the primary analysis. The remaining 10 articles reported only crude HRs or IRRs and were considered in sensitivity analyses 23–32 . No relevant articles were identified from the reference lists of review articles or meta‐analysis studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 49 articles that we included, 39 reported adjusted HRs or IRRs for the outcomes of interest and were included in the primary analysis. The remaining 10 articles reported only crude HRs or IRRs and were considered in sensitivity analyses 23–32 . No relevant articles were identified from the reference lists of review articles or meta‐analysis studies (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 10 articles reported only crude HRs or IRRs and were considered in sensitivity analyses. [23][24][25][26][27][28][29][30][31][32] No relevant articles were identified from the reference lists of review articles or meta-analysis studies (Figure 1). The 49 studies were conducted in 14 different countries, with 15 in Europe, 14 in the United States, 9 in Asia, 3 in the United Kingdom and 8 in other countries (Table 1).…”
Section: Re Sultsmentioning
confidence: 99%
“…Teng et al [ 57 ] compared the preventive tertiary effect between DAAs and peg-IFN-RBV in 301 patients with HCV-HCC by a propensity score corresponding to age, tumor staging, HCC treatment modality and cirrhotic status. The results showed that the tertiary prevention effect lasted in the Peg-IFN/RBV arm ( p < 0.001), but decreased in the DAA arm ( p = 0.135) compared with untreated patients.…”
Section: Comparative Studies Between the Therapeutic Regimens Basementioning
confidence: 99%
“…In a recent study of 301 CHC-HCC patients with curative HCC treatment which adopted the time-varying exposure of different time frames, the incidence rate of HCC recurrence was higher in the DAA arm than in the Peg-IFN/RBV arm during anti-viral therapy (2724.4 vs. 665.8/104 person-years, log-rank p = 0.042) and for a 2-year period after SVR (5259.4 vs. 3277.6/104 person-years, log-rank p = 0.048) [ 148 ], suggesting that the tertiary prevention effect of DAA was brief during antiviral therapy and reduced/absent after the end of treatment. In contrast, a meta-analysis of 15 studies and 2352 CHC-HCC patients found that adjuvant DAA therapy was not associated with higher HCC recurrence (RR 0.62; 95% CI 0.11–3.45; p = 0.56) after adjustment for host and tumor factors [ 147 ].…”
Section: Introductionmentioning
confidence: 99%